Ivan Aleksandăr (1331-1371) Splendore e tramonto del secondo impero bulgaro - ALBERTI, ALBERTO (Biblioteca di Studi Slavistici, 2010)
The long reign of Ivan Aleksandăr (1331-1371), the penultimate emperor of Bulgaria prior to the Turkish conquest, was marked by a series of successful military campaigns against Serbia and Byzantium and above all by an intensive cultural production, largely fostered and funded by the sovereign himself. The central decades of the fourteenth century were of crucial importance for the later cultural evolution of Bulgaria and the whole of Orthodox Slovenia, despite which to date ample and exhaustive studies on the figure of Ivan Aleksandăr are lacking. There is, in effect, a considerable amount of information at disposal, although it is scattered over the literary sources, the colophons of the manuscripts, the epigraphic documentation and also, obviously, the official deeds promulgated by the Emperor. Through the analysis of this varied documentation, this book attempts to reconstruct the figure of the sovereign, the context in which he lived and worked, his greatness and his mistakes and his parallel activities as a strategist and an illuminated patron of the arts. For the first time, the Italian reader can find collected and translated all the manuscript sources relating to the Bulgarian sovereign. The book is completed by an appendix with the original texts of the Slavonic-ecclesiastical tradition.